AUTOPSY REPORT ON NASALIS LARVATUS IN BAKO NATIONAL PARK - Zainal Zahari, Zainuddin; Wahap, Marni; Madinah, Adrus; Siali, Aban; Mohd Tajuddin, Abdullah (Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia, 2023)
An individual of Nasalis larvatus was reported injured by Mr Siali Aban on the 18th January 2012, which was probably due to a fight more than a week ago. However, according to the Bako National Park canteen operator, the animal was first sighted with injury about three weeks ago. The animal was tranquilized by a team of trained UNIMAS staff on the 22 January 2012 using Tilatamine and Zolazepam (Zoletil 100) at a dosage of 3-5 mg per kilogram. Induction time was 9 minutes and recovery occurred after about 60 minutes. Animal was treated with topical antiseptics and the wound dressed. Animal died after 2 ½ hours. Eight ml of blood was collected from the heart about 15 minutes after death. Post mortem was carried out on the 24 January 2012 for 4 hours by Dr Zainal Zahari Zainuddin, assisted and witnessed by Mohd Tajuddin Abdulah, Siali Aban, Wahap Marni, Madinah Adrus and postgraduate students.